TECHNO-ECONOMIC ANALYSIS OF PRODUCTION AND MARKETING OF MARINE BY-PRODUCTS IN INDIA - Sathiadhas, R.; Aswathy, N. (Journal of Indian Fisheries Association, 2015)
Marine by-products coming under the ancillary products group foundmany applications in pharmaceutical and industrial sectors. Although manyof these products are fetching very high price at the export market, adequatestatistics regarding their current production, marketing and utilisation islacking. The present analysis deals with the production potential, level ofexploitation, uses, export growth rate and potential for the future of someof these marine by-products. The analysis revealed that an estimated quantityof 205 tonnes of shells, 10 tonnes of gastropod operculum, 4,932 tonnes ofshark liver oil and 4,384 tonnes of shark cartilage could be produced annuallyin India with the current landings. The production potential of chitin isestimated as 3,560 tonnes from shrimp shell wastes and 1,354 tonnes fromcrab shell wastes. The high unit value of different products clearly indicatesthe scope for their development by evolving appropriate utilisation andmarketing strategies.Keywords: by-products, production potential, marketing, growth rate